Moringa oleifera Seed at the Interface of Food and Medicine: Effect of Extracts on Some Reproductive Parameters, Hepatic and Renal Histology - Attah, Alfred F.; Akindele, Opeyemi O.; Nnamani, Petra O.; Jonah, Ugochukwu J.; Sonibare, Mubo A.; Moody, Jones O. (Frontiers in Pharmacology, 2022)
The lipid-rich Seed of Moringa oleifera has been promoted as an effective water clarifier. Aside its vital nutritional application as an emerging food additive, the seed has continued to gain a wider acceptance in various global ethnomedicines for managing several communicable and lifestyle diseases, howbeit, its potential toxic effect, particularly on fertility and pregnancy outcomes has remained uninvestigated; the effect of Moringa oleifera seed (MOSE) aqueous-methanol extracts on fertility and pregnancy outcome, was investigated in vivo using female Wistar rats that were divided into 50, 100, 300 and 500 mg per kilogram body weight. Group six was given Moringa oleifera seed treated water ad-libitum (ad-libitum group). Organs harvested for histological assessment included ovary, uterus, liver and kidney. In addition to HPLC fingerprint and a preliminary peptide detection, we determined the physico-chemical characteristics and mineral content of MOSE using standard methods. Data were analyzed with significance at p≤0.05. There was no significant difference in the estrus cycle, mating index, gestation survival index, gestation index, fertility index and sex ratio among all groups. Gestation length was reduced in some groups. While the male pup birth weight was comparable among the different groups, female pups' birth weights were significantly reduced in 50 mg and 100 mg groups. Anogenital distance indices of female pups in ad libitum group were significantly increased. Pathologies were observed in the liver and kidneys of dams while kidneys of pups presented a dose-dependent reduction in the number of glomeruli. There were no observed pathological changes in the ovary and uterus. This study showed for the first time in rodents, that the lipid-rich MOSE is unsafe to the kidney of rodents while the lipid-free MOSE appears to be safe at doses up to 300 mg/kg body weight. Findings from this study suggested that the female pups were masculinized. In conclusion, the lipid-rich seed extracts of MOSE appear to be unsafe during pregnancy, induce hepatic and renal toxicity while the lipid-free MOSE excludes inherent toxicity as the hydrophobic part has been linked to toxicity as observed in this study due to the developmental programming effect on female offspring in rodents.